2018
DOI: 10.1159/000496191
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Users with Otosclerosis: Are Hearing and Quality of Life Outcomes Worse than in Cochlear Implant Users without Otosclerosis?

Abstract: Background: The otosclerotic process may influence the performance of the cochlear implant (CI). Difficulty in inserting the electrode array due to potential ossification of the cochlea, facial nerve stimulation, and instability of the results are potential challenges for the CI team. Objectives: To evaluate hearing results and subjective outcomes of CI users with otosclerosis and to compare them with those of CI users without otosclerosis. Method: Retrospective review of 239 adults with bilateral profound pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Five tools were used: Nijmegen Cochlear Implant Questionnaire (NCIQ), Glasgow Benefit Inventory (GBI), Hearing Implant Sound Quality Index, dizziness handicap index, and the Abbreviated Profile of Hearing Aid Benefit. Calvino et al (24) reported statistically significant improvement in all subdomains of the NCIQ after implantation ( p < 0.001) and no statistical difference between NCIQ, GBI, and Hearing Implant Sound Quality Index scores between otosclerotic and nonotosclerotic patient groups. Flook et al (27) reported GBI scores in 20 of 35 patients with a mean of 53, which suggests good benefit from the cochlear implant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five tools were used: Nijmegen Cochlear Implant Questionnaire (NCIQ), Glasgow Benefit Inventory (GBI), Hearing Implant Sound Quality Index, dizziness handicap index, and the Abbreviated Profile of Hearing Aid Benefit. Calvino et al (24) reported statistically significant improvement in all subdomains of the NCIQ after implantation ( p < 0.001) and no statistical difference between NCIQ, GBI, and Hearing Implant Sound Quality Index scores between otosclerotic and nonotosclerotic patient groups. Flook et al (27) reported GBI scores in 20 of 35 patients with a mean of 53, which suggests good benefit from the cochlear implant.…”
Section: Resultsmentioning
confidence: 99%
“…Kraaijenga et al (69) looked only at patients at 1 year of follow-up with unilateral cochlear implantations and did not include PROMs as outcomes. Of the nine studies mentioned previously, three had periods of follow-up over 2 years (range, 60-89.6 mo; minimum, 52 patients) (24,32,56). Two of these studies showed noninferior outcomes (24,32), and one showed significantly better outcomes in the otosclerosis group (56).…”
Section: Audiological Outcomes Versus Other Etiologiesmentioning
confidence: 99%
“…Cochlear implantation is also used in cases of advanced otosclerosis with significant sensorineural hearing loss, or in individuals who developed sensorineural hearing loss after stapes surgery. Individuals with otosclerosis and severe hearing loss show similar quality of life improvement after cochlear implantation as other users of cochlear implants with post-lingual deafness [38].…”
Section: Quality Of Life After Stapes Surgerymentioning
confidence: 88%
“…Patients with advanced otosclerosis may develop cochlear ossification or round window obliteration, requiring an extended cochleostomy. 36,37 Cochlear ossification may impact the electrode-neural interface, affecting performance. 38 Posttraumatic SNHL (eg, temporal bone fracture) may be associated with intracochlear fibrosis.…”
Section: Adult Cochlear Implantationmentioning
confidence: 99%